THE IMPORTANCE OF THE SYNERGISTIC MODEL OF INCREASING INVESTMENT EFFICIENCY IN SMALL INDUSTRIAL ZONES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article discusses the processes associated with the value of the "synergetic model" of improving the efficiency of investments in small industrial zones. Theoretically and methodologically, the factors influencing the process of ensuring investment activity in small industrial zones have been studied. The directions and possibilities of eliminating factors that negatively affect the increase in investment activity of small industrial zones are substantiated. Scientific proposals and practical recommendations are given to increase the investment activity of small industrial zones in Uzbekistan.